Peran Orang Tua Atlet terhadap Prestasi Sepaktakraw Klub Cakrawangsa di Kabupaten Batang - Nunung Purwanti; Boby Agustan (Mutiara Pendidikan dan Olahraga, 2025)
This study aims to describe the role of parents in supporting the achievements of sepak takraw athletes in Batang Regency. Athlete achievement is determined not only by individual abilities and training received, but also by support from their immediate environment, particularly family. In this context, parents play a strategic role in the coaching and development of young athletes, both physically, mentally, and emotionally. This study used a qualitative approach with data collection techniques such as in-depth interviews, direct observation, and documentation. The subjects in this study consisted of parents of sepak takraw athletes, athletes who have achieved success at the regional level, and coaches involved in coaching. Through this approach, comprehensive data was obtained regarding the forms of support provided by parents. The results show that parents play a crucial role in encouraging athlete success. This role is manifested through various forms of support, including moral support in the form of motivation and encouragement, material support such as providing training equipment and transportation costs, and direct involvement in monitoring children's development. Parents also actively communicate and collaborate with coaches and clubs to create a conducive coaching environment. In addition, parents' positive attitudes in appreciating their children's interests and talents contribute to the athletes' high level of self-confidence and commitment. Thus, active parental involvement has been shown to significantly contribute to improving the performance of sepak takraw athletes, particularly at the district level. This research suggests the need for systematic parental involvement in regional sports development programs.